(untitled) (Research, Society and Development, 2023)
Dermatological wounds are anatomical disorders that result in changes in the physiology of the skin. The use of ozone therapy for dermatological wounds acts against pathogens and helps in tissue regeneration. The objective of the article was an integrative review of the literature on the role of the pharmacist in ozone therapy for the treatment of dermatological wounds. The following databases were used: LILACS, MEDLINE, SCIELO, ResearchGate, ScienceDirect® and Google Scholar. The inclusion criteria were literature published in Portuguese, English and Spanish available in full and free of charge, the stipulated period was from 2013 to 2023, and excluded paid and duplicate literature. 21 references were selected, 14.28% (3) in English and 85.71% (18) in Portuguese. The methodological processes present in the literature are 61.90% (13) literature review, 19.04% (4) experimental studies, 9.52% (2) case reports, 4.76% (1) clinical protocol, 4 .76% (1) retrospective cohort study, 4.76% (1) resolution and 9.52% (2) regulations. 76.19% (16) were used from Scielo, 9.52% (2) from MEDLINE and 14.28% (3) from Google Scholar. Dermatological wounds are classified: acute and chronic wounds. The use of ozone therapy has antimicrobial effects and proves to be a quick, economical and efficient method. The pharmacist’s participation is supported by CFF resolutions 572/2013 and 685/2020. There is a need for more studies, which show the presence of the pharmacist in the practice of ozone therapy, in monitoring and improving patients with dermatological wounds.